A Bandwidth-improved slotted circular microstrip antenna (CMSA) for High Altitude Platform Stations (HAPS) - Ezanuddin, A. A. M.; Mohd Fareq, Malek; Soh, Ping Jack; R. Badlishah, Ahmad, Assoc. Prof. Dr. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/